Volume 5: Materials Technology; Petroleum Technology 2014
DOI: 10.1115/omae2014-23643
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Zone Microstructure Associated With Embrittlement of Subsea Dissimilar Joints

Abstract: Within subsea oil and gas systems, nickel alloy filler metals are commonly used in the joining of ferritic steels with different mechanical properties. An example of this is the joining of low alloy steel (LAS) forged manifold hubs (e.g 8630 or F22) to low hardenability pipelines steels, such as X65). The joint is part of a two stage welding process that simplifies offshore installation. Initially, a weld deposit is made on the forging using a multi-pass ‘buttering’ technique, providing intermediate layers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 0 publications
1
16
0
7
Order By: Relevance
“…However, at typical PWHT temperatures the carbon activity in the weld metal remains comparatively low. This is attributed to the diffusivity in the austenite being considerably smaller than in the ferrite and the solubility of the carbon is higher 22 .…”
Section: Dissimilar Interface Microstructure In the Aswelded And Aftementioning
confidence: 99%
See 4 more Smart Citations
“…However, at typical PWHT temperatures the carbon activity in the weld metal remains comparatively low. This is attributed to the diffusivity in the austenite being considerably smaller than in the ferrite and the solubility of the carbon is higher 22 .…”
Section: Dissimilar Interface Microstructure In the Aswelded And Aftementioning
confidence: 99%
“…The thickness of this zone varied and, in general, had a dimension of approximately 10μm. Dodge et al 22 found a planar zone with a thickness of 32 μm, applying a lower welding energy. A positive factor in reducing the thickness of zone Φ is the inhibition of formation of Cr 7 C 3 -type carbides in this zone, which may arise mainly after prolonged PWHT 22 .…”
Section: Dissimilar Interface Microstructure In the Aswelded And Aftementioning
confidence: 99%
See 3 more Smart Citations